Philosophising gender politics in Y: The Last Man. Issue 2 (2nd April 2016) - Khng, Desiree L.
Abstract : Patriarchy is threatened in Brian K. Vaughan's apocalyptic graphic novel series Y: The Last Man, denoted through the near-extinction of males on earth. This study incorporates modern critical theory and philosophy in the analysis of Vaughan's comics. Thematically, this essay employs works by Judith Butler, Joan Riviere and Sigmund Freud regarding the analysis of gender, sex and feminism. Because Y: The Last Man incorporates religious and scientific philosophy as a framework for its gender theme, this essay focuses on the impact of an all-female dystopia on patriarchal laws and their adaptations, which in turn determine the evolution of normative social relations post-apocalypse.